Crime and punishment in Sweden: historical criminal justice statistics 1750-2000 - Hofer, Hanns von (Journal of Scandinavian studies in criminology and crime prevention, 2003)
The article is a summary of a book in Swedish on the development of crime (that is, violence and theft) and punishment in Sweden in a historical perspective. The data stem mostly from conviction statistics. Following a discussion of the reliability of conviction statistics, trends in these statistics are described and various criminological explanations for these trends are discussed